Radiation induced dermatitis following infrared radiation (IR) therapy in a diagnosed case of systemic lupus erythematosus (SLE): a case report - Sah, Sunny Kumar; Amatya, Amit; Kafle, Monique; Upadhyaya, Smarika (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Infrared radiation is increasingly being used for cosmetic and wellness purposes. Repeated exposure to source of Infrared radiation results in a skin lesion described as erythema ab igne. Instead patients land up with life threatening complication like our case. In this article we present to you a 39-year-old female who presented with skin lesions after she underwent radiation therapy. We have included clinical findings of the case with review of the literature